The Impact of Adipose Tissue–Derived miRNAs in Metabolic Syndrome, Obesity, and Cancer - Heyn, Gabriella Simões; Corrêa, Luís Henrique; Magalhães, Kelly Grace (Frontiers in Endocrinology, 2020)
Obesity is a multifactorial and complex condition that is characterized by abnormal and excessive white adipose tissue accumulation, which can lead to the development of metabolic diseases, such as type 2 diabetes mellitus, nonalcoholic fatty liver disease, cardiovascular diseases, and several types of cancer. Obesity is characterized by excessive adipose tissue accumulation and associated with alterations in immunity, displaying a chronic low-grade inflammation profile. Adipose tissue is a dynamic and complex endocrine organ composed not only by adipocytes but several immunological cells, which can secrete hormones, cytokines, and many other factors capable of regulating metabolic homeostasis and several critical biological pathways. Remarkably, adipose tissue is a major source of circulating microRNAs (miRNAs), recently described as a novel form of adipokines. Several adipose tissue-derived miRNAs are deeply associated with adipocytes differentiation and have been identified with an essential role in obesity-associated inflammation, insulin resistance, and tumor microenvironment. During obesity, adipose tissue can completely change the profile of the secreted miRNAs, influencing circulating miRNAs and impacting the development of different pathological conditions, such as obesity, metabolic syndrome, and cancer. In this review, we discuss how miRNAs can act as epigenetic regulators affecting adipogenesis, adipocyte differentiation, lipid metabolism, browning of the white adipose tissue, glucose homeostasis, and insulin resistance, impacting deeply obesity and metabolic diseases. Moreover, we characterize how miRNAs can often act as oncogenic and tumor suppressor molecules, significantly modulating cancer establishment and progression. Furthermore, we highlight in this manuscript how adipose tissue-derived miRNAs can function as important new therapeutic targets.